Constitution of the State of Jefferson, Articles 1st & 2nd, Boundaries and Bill of Rights - Byers, Wm. N. (William Newton), 1831-1903 (1859)
Draft of the first 2 articles of a constitution for the proposed state of Jefferson written by a committee of persons in the unrecognized Jefferson Territory, then the western part of Kansas Territory, now Colorado.